Adaptive Statistical Iterative Reconstructions Technique (ASIR) Impact on Both Image Quality and Dose in CT Chest Examination - Isam, Mariam; Mokhtar, Ayman; Abdelrazek, A.; EL Mogy, Sabry; Oraby, A.H. (JOURNAL OF ADVANCES IN PHYSICS, 2018)
The main objective of the presented study was to estimate the influence of Adaptive Statistical Iterative Reconstruction (ASIR) algorithm on image and dose Image Quality in Chest CT (Computed tomography) examination compared with the FBP (Filter back projection) techniques.